Implementation of the Jigsaw Learning Method in Teaching the Reading of the Yellow Book for Santri at Dayah Terpadu Bustanul Arifin Bener Meriah Academic Year 2024-2025 - Agus Readi (Education Achievement: Journal of Science and Research, 2024)
This qualitative study explores the implementation of the Jigsaw Learning Method in teaching the reading of the Yellow Book to students (santri) at Dayah Terpadu Bustanul Arifin, Bener Meriah, during the academic year 2024-2025. The method involves several key steps: First, students are divided into Core Groups by the ustadz (teacher). These Core Groups are then transitioned into Expert Groups, where each group focuses on specific areas such as Nahwu (Arabic grammar), Shorrof (morphology), Reading and Meaning, and Explanation. Students engage in in-depth discussions within these Expert Groups to enhance their understanding of the topics. Following the discussions, students return to their Core Groups to present and share the knowledge gained. Finally, the ustadz concludes the session with a 10-minute summary, consolidating the main points and addressing any questions. This study highlights the structured and collaborative nature of the Jigsaw Learning Method in fostering a deeper comprehension and engagement with the traditional texts.